High final energy of low-level gallium arsenide laser therapy enhances skeletal muscle recovery without a positive effect on collagen remodeling - Assumpcao de Freitas, Carlos Eduardo [UNESP]; Bertaglia, Raquel Santilone [UNESP]; Vechetti Junior, Ivan Jose [UNESP]; Mareco, Edson Assuncao [UNESP]; Simoes Salomao, Rondinelle Artur [UNESP]; Paula, Tassiana Gutierrez de [UNESP]; Nai, Gisele Alborghetti; Carvalho, Robson Francisco [UNESP]; Pacagnelli, Francis Lopes; Dal-Pai-Silva, Maeli [UNESP] (Wiley-Blackwell, 2015)
The aim of this study was to evaluate the effects of a Gallium Arsenide (GaAs) laser, using a high final energy of 4.8J, during muscle regeneration after cryoinjury. Thirty Wistar rats were divided into three groups: Control (C, n=10); Injured (I, n=10) and Injured and laser treated (Injured/LLLT, n=10). The cryoinjury was induced in the central region of the tibialis anterior muscle (TA). The applications of the laser (904nm, 50mW average power) were initiated 24h after injury, at energy density of 69Jcm(-1) for 48s, for 5days, to two points of the lesion. Twenty-four hours after the final application, the TA muscle was removed and frozen in liquid nitrogen to assess the general muscle morphology and the gene expression of TNF-, TGF-, MyoD, and Myogenin. The Injured/LLLT group presented a higher number of regenerating fibers and fewer degenerating fibers (P<0.05) without changes in the collagen remodeling. In addition, the Injured/LLLT group presented a significant decrease in the expression of TNF- and myogenin compared to the injured group (P<0.05). The results suggest that the GaAs laser, using a high final energy after cryoinjury, promotes muscle recovery without changing the collagen remodeling in the muscle extracellular matrix.